Economic Television Media and Shaping Public Trends - Al-Hamadani, Omar Ayyed Abed; radhi, wisam Fadhil (ALBAHITH ALALAMI, 2022)
The problem of this paper is identified by knowing the role of the economic television media in shaping the audience's attitudes. It seeks to understand the type of relationship between the dependence of the economic elite audience on news bulletins and its cognitive implications. The categories of Iraqi society, namely, the economic elite category. This paper adopted the descriptive survey method for the period from 3/1/2022 - 6/31/2022. The sample was extracted according to the relative stratified sampling method in the city of Baghdad. A set of results has been concluded, the most prominent of which is the public's heavy reliance on economic news bulletins to obtain news and information, as indicated by (63%) of the respondents participating in the research sample.